Dominant personality characteristics of Roxas City elective Pffice aspirants and their reasons for candidacy. - Ardivilla, Gerreon O.
This is a study on the personality characteristics of Roxas City political office aspirants. This was conducted to identify the dominant personality characteristics of Roxas City political office aspirants; To identify their dominant personality characteristics in relation to the position they aspire for; and to determine the reason for fielding themselves to the position they aspire for. The study hypothesizes that there is no significant difference in the dominant personality characteristics of the Roxas City elective office aspirants in relation to the elective positions aspired for., Through the use of the Edwards Personal Preference Schedule, the dominant personality characteristics of the respondents were identified as (by ranking): nurturance,succorance, affiliation, autonomy, exhibition, deference, abasement, and aggression. The findings are supportive of the hypothesis. Through use of an open-ended questioNnaire, the reasons for candidacy of the respondents was determined. Serving the people of Roxas City has the most responses. Consistency on the response was noted on the questions on the factors that made them decide to run, the importance and significance of their candidacy. The study suggests the use of etic and emic approach to further establish the personality characteristics of the Roxas City elective office aspirants.